Does getting a mortgage affect credit card use? - Scott L. Fulford; Joanna Stavins (Federal Reserve Bank of Boston, 2019)
Buying a house changes a household's balance sheet by simultaneously reducing liquidity and introducing mortgage payments, which may leave the household more exposed to other shocks. We find that this change affects credit card use in two ways: A debt effect increases credit card spending, while a credit effect leads to higher credit limits. In the short run, a new mortgage acquisition has a robust and statistically significant positive effect on credit card utilization - the fraction of a consumer's credit card limit that is used - of approximately 11 percentage points. Before the 2008 financial crisis, the credit effect exceeded the debt effect in the long run, pushing down long-term utilization. In our sample period after the financial crisis, the debt effect dominated in the long run, and credit card utilization rates rose upon the acquisition of a new mortgage, consistent with larger down payments leaving households more constrained.
Keywords: D14; D15; E21; 330; credit cards; mortgage; credit card utilization; debt